Career management to carrier advice - Ilić Đurđijana; Janjić Ivana; Ilić Slađana (Trendovi u Poslovanju)
A strong motivation and motivation for individuals in the organization is an opportunity for advancement. This opportunity is showing its importance already at the stage of recruiting or attracting people for the organization. "Career Development and Career Development Policy should be a permanent activity of the human resource sector, which is expected to create objective criteria for the advancement and shift of employees from low-ranking to higher and high-ranking positions, that this move would not be a matter of good will individual and personal sympathies, but a standard that, once the conditions are met, is automatically applied." [1] In order to properly understand the importance of careers for each individual, but also for the organization, it is necessary to consider the importance of the career management process, especially through career counseling, because "career management implies encouraging and encouraging people to learn and improve their skills by organizing different types of education and selecting the appropriate individuals in the groups of students whose career is seriously considered".[1]